2017
DOI: 10.1371/journal.pone.0180358
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-spatial cueing in children with differential reading and spelling profiles

Abstract: Dyslexia has been claimed to be causally related to deficits in visuo-spatial attention. In particular, inefficient shifting of visual attention during spatial cueing paradigms is assumed to be associated with problems in graphemic parsing during sublexical reading. The current study investigated visuo-spatial attention performance in an exogenous cueing paradigm in a large sample (N = 191) of third and fourth graders with different reading and spelling profiles (controls, isolated reading deficit, isolated sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
2
4
0
2
Order By: Relevance
“…But even if the numerical trend did not reach significance, the variable visual attention revealed interesting results nevertheless, because Cluster 1, the cluster with deficits in visual magnocellular function, also had numerically worse results in visual attention than Cluster 2 and the normally spelling children. With respect to visual attention skills, similarities to results by Banfi et al (2017) can be pointed out, who investigated visuo-spatial attention skills in dyslexic and dysgraphic children. In their study, a difference between poor readers and writers was also detected with respect to a right-over-left advantage (position effect) for dyslexics and no position effect for dysgraphic children.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…But even if the numerical trend did not reach significance, the variable visual attention revealed interesting results nevertheless, because Cluster 1, the cluster with deficits in visual magnocellular function, also had numerically worse results in visual attention than Cluster 2 and the normally spelling children. With respect to visual attention skills, similarities to results by Banfi et al (2017) can be pointed out, who investigated visuo-spatial attention skills in dyslexic and dysgraphic children. In their study, a difference between poor readers and writers was also detected with respect to a right-over-left advantage (position effect) for dyslexics and no position effect for dysgraphic children.…”
Section: Discussionsupporting
confidence: 57%
“… Bosse et al (2007) reported that both visual attention deficits as well as a phonological disorder can be associated with dyslexia, thus causing reading problems for different reasons. Banfi et al (2017) investigated visuo-spatial cueing effects for children with isolated reading and spelling problems as well as a combined disorder. In contrast to children with an isolated reading or spelling disorder, children with a combined reading and spelling deficit showed a cueing deficit, which means, no significant difference in reaction time between valid and invalid cues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Right spelling as a skill means being precise; the habit of being correct is one of the essential virtues to be acquired by educated persons. Precision is important for communication, especially for the person who is receiving the information, while it is highly significant for the person who wishes to construct the communication (Banfi et al, 2017). Spelling precision can be viewed from two different dimensions: accuracy and stability.…”
Section: The Case For Good Spellingmentioning
confidence: 99%
“…All participants having an RT difference (Block 12 minus Block 11) smaller than 35.17 ms were classified as 'non-learners', whereas all participants above the threshold of 35.17 ms were classified as 'learners'. This method is based on a previous study of visual cueing in reading and spelling deficit (Banfi et al, 2017). After categorizing participants, chi-squared tests were applied to determine whether the number of learners differed by group (PD vs. HC).…”
Section: Cuesmentioning
confidence: 99%